Effectiveness of Behavioral Ivan Pavlov Conservation sociodrama The with techniques to Increase Characters Help Others Through Lesson Study - Ni Komang Indah Resti Handayani; I Nyoman Dantes; I Ketut I Ketut Darsana (International Conference on Technology and Educational Science)
This study aims to determine the effectiveness of behavioral counseling Ivan Pavlov with sociodrama techniques to improve the character of helping others through lesson study in student's first grade. This type of research is quasi-experimental with pre-test and post-test control group design. The sample is 20 students with df 19. The method of collecting data using character questionnaires helps other people as many as 30 items. The results of data analysis are the value of to. tcount 3.188 > ttable 2.09 so that Ho is rejected, and Ha is accepted. So there are significant differences. It can be concluded that Ivan Pavlov's behavioral counseling techniques for effective sociodrama to improve character help others.